2003
DOI: 10.1099/mic.0.26619-0
|View full text |Cite
|
Sign up to set email alerts
|

A polyketide synthase gene required for ochratoxin A biosynthesis in Aspergillus ochraceus

Abstract: Ochratoxin A is an important nephrotoxic and nephrocarcinogenic mycotoxin, produced by Aspergillus ochraceus as a polyketide-derived secondary metabolite. A portion of a putative polyketide synthase gene ( pks) involved in the biosynthesis of this mycotoxin was cloned by using a suppression subtractive hybridization PCR-based approach. The predicted amino acid sequence of the 1?4 kb clone shared 28-35 % identity to acyl transferase regions from fungal polyketide synthases found in the databases. Based on rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
113
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(124 citation statements)
references
References 39 publications
2
113
0
2
Order By: Relevance
“…This cluster is absent from the genomes of other sequenced aspergilli such as A. fumigatus, A. oryzae and A. nidulans [8][9][10] . A putative ochratoxin cluster was identified on the basis of a PKS fragment of A. ochraceus involved in ochratoxin biosynthesis 41 . Some A. niger strains have been reported to synthesize this toxin but little is known about the biosynthetic pathway 42 .…”
Section: Secondary Metabolism and Safetymentioning
confidence: 99%
“…This cluster is absent from the genomes of other sequenced aspergilli such as A. fumigatus, A. oryzae and A. nidulans [8][9][10] . A putative ochratoxin cluster was identified on the basis of a PKS fragment of A. ochraceus involved in ochratoxin biosynthesis 41 . Some A. niger strains have been reported to synthesize this toxin but little is known about the biosynthetic pathway 42 .…”
Section: Secondary Metabolism and Safetymentioning
confidence: 99%
“…The strains UEL91 and ITAL163 were selected for the purpose of this research because they showed expressive level of genetic similarity as revealed by RAPD profiles, but contrasted for their ability to produce OTA. This tactic was chosen as an alternative to that adopted by other authors [5,13], who have made comparisons of gene expression in a single strain growing in two different media (permissive and restrictive medium for OTA production) in order to minimize the detection of transcripts not related to OTA biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Despite of its importance, only a small number of genes were designed to be involved in the biosynthetic pathway of OTA in Aspergillus species. These include P450 monoxygenase, nonribosomal peptide synthetase, chloroperoxidase and polyketide synthase genes [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data has shown that this step requires the activity of a polyketide synthase 26 . Furthermore, the gene encoding polyketide synthase appears to be very different between Penicillium and Aspergillus species 26,46 .…”
Section: Biosynthesis Of Ochratoxin a And Ochratoxin A Producing Micrmentioning
confidence: 99%
“…Recent data has shown that this step requires the activity of a polyketide synthase 26 . Furthermore, the gene encoding polyketide synthase appears to be very different between Penicillium and Aspergillus species 26,46 . In A. ochraceus, the gene of polyketide synthase is expressed only under OTA permissive conditions and only during the early stages of mycotoxin synthesis 26 .…”
Section: Biosynthesis Of Ochratoxin a And Ochratoxin A Producing Micrmentioning
confidence: 99%